2012
DOI: 10.1016/j.drugpo.2011.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Where harm reduction meets housing first: Exploring alcohol's role in a project-based housing first setting

Abstract: Background Housing first (HF) programmes provide low-barrier, nonabstinence-based, immediate, supportive and permanent housing to chronically homeless people who often have co-occurring substance-use and/or psychiatric disorders. Project-based HF programmes offer housing in the form of individual units within a larger housing project. Recent studies conducted at a specific project-based HF programme that serves chronically homeless individuals with alcohol problems found housing provision was associated with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 26 publications
4
93
0
Order By: Relevance
“…Only a handful of such studies have been undertaken. For example, Collins et al, 2012b found that alcohol consumption played a multifaceted role in the lives of residents living in the Seattle program. From the point of view of residents interviewed, the benefits of living in the program included avoiding withdrawal and feeling part of a supportive local community.…”
Section: Introductionmentioning
confidence: 98%
“…Only a handful of such studies have been undertaken. For example, Collins et al, 2012b found that alcohol consumption played a multifaceted role in the lives of residents living in the Seattle program. From the point of view of residents interviewed, the benefits of living in the program included avoiding withdrawal and feeling part of a supportive local community.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, having to negotiate social relationships that are made complicated when one person has housing while others still live on the streets could be challenging. The question of location also highlights differences in approaches to HF that use either a single-site housing model with limited choice in location (Collins et al, 2011) or a scatter-site model that offers more choice of location (Tsemberis et al, 2004). In this case, consumers did not have choice of their new neighborhood given a single-site approach.…”
Section: Theme 3: Neighborhood Mattersmentioning
confidence: 99%
“…To address HIV alone would entail missing many of the social determinants of health that lead to high HIV incidence in the population (MacKellar et al, 2005; Phillips et al, 2011). It is essential that HIV prevention efforts in the HBC include providing resources and/or linkages to resources that provide general education, employment training and assistance, substance abuse programs, housing assistance, as well as mental health services (Collins et al, 2012; Dworkin et al, 2008; Lehavot et al, 2011). To this end, partnerships with various CBOs are essential, as such entities can help to address the various needs of the community in question and to ensure sustainability beyond academic funding and research grants.…”
Section: Discussionmentioning
confidence: 99%